Seasoning Practices and Manufacturing Operations Followed by Various Wood Working Industries of U.S.A., Canada and England - Rehman, M. A. (Indian Forester, 1950)
The article describes the method of handling sawn material in the timber yards and manufacturing concerns of U.S.A., Canada and England. It states that every timber industry of the West has developed a technique of its own for seasoning wood, which it finds the best and cheapest for its requirements. The details of the method of seasoning wood for shuttles and bobhins are given, along with a brief description of the manufacturing operations of the same.